Learning lab as a utopian methodology for future making: Decolonizing knowledge production toward racial justice in school discipline - Ko, Dosun; Bal, Aydin; Bird Bear, Aaron; Orie, Linda; Mawene, Dian (Mind, Culture, and Activity, 2023)
Click on the DOI to access this article (may not be free). Students from minoritized communities in US public schools face harsher exclusionary discipline, leading to negative academic, social, and emotional outcomes. Racial disproportionality in school discipline is a critical inequity that requires ecologically valid solutions with local stakeholders. The Indigenous Learning Lab (ILL) was implemented to address racial disproportionality that American Indian students experience at a rural high school serving a band of an Anishinaabe nation in the United States. ILL is an inclusive systemic design process informed by cultural historical activity theory and decolonizing methodology. This study explores how ILL facilitated local stakeholders' utopian future-making by means of Ruth Levitas's (2013) three modes of utopian methodology - utopia as archeology, architecture, and ontological becoming - to dismantle an oppressive settler-colonial school discipline system.